The role of the Local Government Sector Education and training Authority in the skills development programme of the Capricorn District Municipality. - Moja, Moshakobo Johannes (My University, 2010)
Skills development plays an important role in the growth of every country‟s economy, service delivery and technology improvement. It builds confidence and dignity in people, so it is crucial for every government to ensure that its people are well-skilled and developed. Hence the formation of Sector Education and Training Authority which ensures that employees are also trained in their workplace; this initiative is also meant to address imbalances of the past. Local Government Sector Education and Training Authority were established to ensure skills development within the local government sector. Local government (municipalities) is the third sphere of government which interacts very closely with the community and delivers basic services like water and sanitation, roads, electricity, refuse removal, housing and other essential services. For all these services to be provided efficiently and effectively the municipality needs competent and skilled employees, if they do not have the skilled employees they will have challenges in delivering these services. Proper training and development is continuously needed as technology changes and new developments are uncovered in the industry. It will be imperative for the municipalities to work in hand with Local Government Sector Education and Training Authority to ensure that training and development is delivered to the employees, and funding is allocated every year. Continuous research need to be conducted to ensure best practices of training and development are adhered to. The qualitative research method was followed for this research. A questionnaire was used to collect the data from participants and a follow-up interview was conducted with participants. During the follow-up interviews a number of supporting documents were received. Two people from each of the six municipalities took part in the research totaling twelve participants. It was discovered that Local Government Sector Education and Training Authority helps the municipalities with skills development issues, though there are gaps which still need to be closed. Municipalities are also making efforts to ensure that their employees are skilled. However, municipalities can still improve their skills analysis processes, implement performance management system for their employees and increase their training and development budget.
Thesis (MBA)--University of Limpopo, 2010.
Keywords: Education & Development Sector; Skills Development; Local Government; 320.83; Skills development